Stabilisasi Tanah dan Semen Sebagai Peningkatan Karakteristik Tanah - Eriq Setiawan; Syahrul Syahrul; Findia Findia (Department of Architecture, Faculty of Engineering, 2022)
Clay soil is a soil composed of various materials, including kaolinite, montmorillinite and illite group. The mineral montmorillinite has a sensitivity to the influence of water, it is very easy to expand and shrink. The level of swelling and shrinkage of clay soil is determined by the high and low content of montmorillinite in the clay grains. To improve soil properties, stabilization of the soil is carried out by including testing the physical and mechanical properties of the soil. in this study using the addition of a percentage of 5%, 10%, and 15% cement, stabilization with cement affects the decrease in the properties of the plasticity index, the compressive strength test increases and the CBR (california bearing ratio) increases. Soil improvement occurred at 15% stabilization cement percentage.Tanah lempung merupakan tanah yang tersusun dari berbagai material antara lain kaolinite,montmorillinite dan illite group. Mineral montmorilinite mempunyai kepekaan terhadap pengaruh air, sangat mudah untuk mengembang dan menyusut. Tinggi rendahnya tingkat kembang (swelling) dan susut (shrinkage) tanah lempung ditentukan oleh tinggi rendahnya kandungan montmorilinite pada butiran lempung. Untuk memperbaiki sifat tanah dilakukan stabilisasi terhadap tanah dengan mencakup pengujian sifat fisis tanah dan mekanis. pada penelitian ini menggunakan penambahan presentase 5%,10%, dan 15% semen, stabilisasi dengan semen berpengaruh terhadap penurunan sifat indeks platisitas, uji kuat tekan meningkat dan CBR (california bearing ratio) meningkat. Perbaikan tanah terjadi pada presentase semen stabilisasi 15%.